Attention Test as a Predictive Marker of Vasospasm in Patients with Aneurysmal Subarachnoid Hemorrhage - Helaina Lehrer; Ankit Bansal; Nicki Mohammadi; Anmol Mittal; John Liang; Alexandra S. Reynolds (Clinical and Translational Neuroscience)
Aneurysmal subarachnoid hemorrhage (aSAH) has high morbidity and mortality in part due to vasospasm and delayed cerebral ischemia (DCI). This retrospective, single-center, case–control study evaluates the accuracy of an attention test, counting backwards from twenty to one (TTO), for detecting vasospasm and DCI in patients admitted to the ICU with aSAH over one year. The odds of symptomatic vasospasm and hospital outcomes were compared between the inattention and control groups. A subgroup analysis included accuracy tests comparing TTO to radiographic vasospasm. Of 44 subjects, 24 had inattention during their ICU course. Compared to controls, the inattention group had increased odds of vasospasm (OR 72 [7.6–677.7], p = 0.001), with significantly longer ICU (5.9 days) and hospital (6.6 days) lengths of stay, and higher odds of discharge to other healthcare facilities (OR 11.4 [2.8 to 46.8], p < 0.001). Errors on TTO testing had a specificity and sensitivity of 78%, and a positive predictive value (PPV) of 91%, for radiographic vasospasm, primarily in the anterior circulation. This study provides support for future prospective research to help elucidate the utility of TTO testing for monitoring and treatment of patients with aSAH.